Protonated Ethylene Carbonate: A Highly Resonance‐Stabilized Cation. Issue 12 (17th November 2021) - Beck, Stefanie; Jessen, Christoph; Kornath, Andreas J.
Abstract: Salts containing the monoprotonated ethylene carbonate species of were obtained by reacting it with the superacidic systems X F/ M F5 ( X =H, D; M =Sb, As). The salts in terms of [C3 H5 O3 ] + [SbF6 ] −, [C3 H5 O3 ] + [AsF6 ] − and [C3 H4 DO3 ] + [AsF6 ] − were characterized by low‐temperature infrared and Raman spectroscopy. In order to generate the diprotonated species of ethylene carbonate, an excess of Lewis acid was used. However, this only led to the formation of [C3 H5 O3 ] + [Sb2 F11 ] −, which was characterized by a single‐crystal X‐ray structure analysis. Quantum chemical calculations on the B3LYP/aug‐cc‐PVTZ level of theory were carried out for the [C3 H5 O3 ] + cation and the results were compared with the experimental data. A Natural Bond Orbital (NBO) analysis revealed sp 2 hybridization of each atom belonging to the CO3 moiety, thus containing a remarkably delocalized 6π‐electron system. The delocalization is confirmed by a 13 C NMR‐spectroscopic study of [C3 H5 O3 ] + [SbF6 ] − . Abstract : The protonation of ethylene carbonate succeeded in the superacidic media HF/ M F5 ( M =Sb, As). Surprisingly, the cation displays a highly 6π‐electron resonance stabilized CO3 moiety.